Land characterization and management in the marine-volcanic area of Mount Semeru, Indonesia: A case study of sugarcane commodities - Basuki, Basuki; Adib , Affan Rizwanda; Destiawan, Hisyam Azhar; Sari, Vega Kartika (Brawijaya University, 2025)
Indonesia has targeted achieving national sugar self-sufficiency in 2035 through intensification and extensification. Marginal land, including in geological formation areas originating from marine-volcanic influences, is considered for utilization. Efforts to increase the productivity of sugarcane cultivation land on marginal land require an evaluation of the suitability of varieties and fertilizer inputs. The study aimed to characterize and manage land in the marine-volcanic area of ??Mount Semeru for sugarcane cultivation. The method used to answer the challenges of marginal land for sugarcane cultivation was divided into stages: environmental identification, climate identification, soil characteristic identification, resistant typology evaluation, sugarcane maturity type evaluation, variety suitability identification, and fertilizer dosage. The results of the study showed that marine-volcanic land can be utilized for sugarcane cultivation to produce high productivity above 80 t/ha by placing location-specific varieties and appropriate fertilizer management. Environmental and soil characteristics include rainfall of >2,000 mm/year and flat-sloping land topography dominated by an average sand texture fraction of > 30%. The appropriate varieties are Kidang Kencana, Bululawang/, NXI 4T, VMC 76-16, VMC 86-550, and NX03. The type of maturity of sugarcane varieties at the research location partly changed, such as the NX03 and VMC 76-16 varieties, which were originally middle-late ripe and changed to early-middle, which affected the fertilizer given at each location and the influence of clay percentage. The amount of fertilizer in the research area on average for plantcane was 151.75 kg/ha, 62 kg/haP2O5, and 103.5 kg/haK2O, and for ratoon 227.63 kg/ha, 38 kg/haP2O5, and 146.5 kg/haK2O.